Death Associated Protein Kinases: Molecular Structure and Brain Injury - Nair, Syam (Molecular Diversity Preservation International (MDPI), 2013)
Perinatal brain damage underlies an important share of motor and neurodevelopmental disabilities, such as cerebral palsy, cognitive impairment, visual dysfunction and epilepsy. Clinical, epidemiological, and experimental studies have revealed that factors such as inflammation, excitotoxicity and oxidative stress contribute considerably to both white and grey matter injury in the immature brain. A member of the death associated protein kinase (DAPk) family, DAPk1, has been implicated in cerebral ischemic damage, whereby DAPk1 potentiates NMDA receptor-mediated excitotoxicity through interaction with the NR2BR subunit. DAPk1 also mediate a range of activities from autophagy, membrane blebbing and DNA fragmentation ultimately leading to cell death. DAPk mRNA levels are particularly highly expressed in the developing brain and thus, we hypothesize that DAPk1 may play a role in perinatal brain injury. In addition to reviewing current knowledge, we present new aspects of the molecular structure of DAPk domains, and relate these findings to interacting partners of DAPk1, DAPk-regulation in NMDA-induced cerebral injury and novel approaches to blocking the injurious effects of DAPk1.